2020
DOI: 10.3390/antiox9080760
|View full text |Cite
|
Sign up to set email alerts
|

BKCa Channels as Targets for Cardioprotection

Abstract: The large-conductance calcium- and voltage-activated K+ channel (BKCa) are encoded by the Kcnma1 gene. They are ubiquitously expressed in neuronal, smooth muscle, astrocytes, and neuroendocrine cells where they are known to play an important role in physiological and pathological processes. They are usually localized to the plasma membrane of the majority of the cells with an exception of adult cardiomyocytes, where BKCa is known to localize to mitochondria. BKCa channels couple calcium and voltage responses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 130 publications
(258 reference statements)
0
44
0
Order By: Relevance
“…Interestingly, a large conductance, calcium-activated K + channel (BK Ca ), expressed on the plasma membrane of most cell types but characteristically found on the inner mitochondrial membrane of adult cardiomyocytes (mitoBK Ca ), has been shown to confer protection from IRI by increasing the mitochondrial calcium capacity and reducing ROS production [ 36 ]. Increased ROS production during preconditioning triggers the opening of the mitoBK Ca channel, leading to a K + influx in mitochondria with an ensuing reduction in Ca 2+ influx and internal membrane depolarization, overall preventing calcium overload, MPTP opening, and cardiomyocyte death.…”
Section: Mitochondrial Dysfunction and Cardiovascular Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a large conductance, calcium-activated K + channel (BK Ca ), expressed on the plasma membrane of most cell types but characteristically found on the inner mitochondrial membrane of adult cardiomyocytes (mitoBK Ca ), has been shown to confer protection from IRI by increasing the mitochondrial calcium capacity and reducing ROS production [ 36 ]. Increased ROS production during preconditioning triggers the opening of the mitoBK Ca channel, leading to a K + influx in mitochondria with an ensuing reduction in Ca 2+ influx and internal membrane depolarization, overall preventing calcium overload, MPTP opening, and cardiomyocyte death.…”
Section: Mitochondrial Dysfunction and Cardiovascular Disordersmentioning
confidence: 99%
“…Experimental studies showed promising results as administration of fission proteins inhibitors reduced MI size and improved mitochondrial function in rodents [ 39 ], but more recent data did not confirm such findings and point to possible inhibitor-related mitochondrial damage [ 40 ]. Similarly, results from studies exploring the therapeutic benefits of mitoBK Ca channel activation are on the rise; mitoBK Ca agonists include both synthetic substances (NS1619, NS11021 [ 41 ]) and many endogenous molecules, including nitric oxide, carbon monoxide (CO), and hydrogen sulfide [ 36 ].…”
Section: Mitochondrial Dysfunction and Cardiovascular Disordersmentioning
confidence: 99%
“…Cardiac tissue mitochondria contain two potassium channels that can be treated as calcium sensors since they are activated by calcium ions. The first channel belonging to this group was the large-conductance calcium-activated potassium (mitoBK Ca ) channel, which was found in mitochondria of mammalian heart tissue and in cardiac-derived cell lines [ 11 , 38 , 92 , 93 , 94 , 95 ]. These channels are also present in the mitochondria of other tissues such as brain, skeletal muscle, bronchial epithelium or skin fibroblasts [ 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ].…”
Section: Mitochondrial Calcium-activated Potassium Channelsmentioning
confidence: 99%
“…BK Ca channels are also present in other organelles [ 101 , 102 , 104 ]. However, it is believed that in cardiomyocytes, BK Ca channels are present exclusively in mitochondria and are not found in the plasma membrane [ 11 , 105 ]. Here, we briefly present key findings that describe cardiac mitoBK Ca channels, and more details are presented in excellent papers [ 11 , 105 , 106 ].…”
Section: Mitochondrial Calcium-activated Potassium Channelsmentioning
confidence: 99%
See 1 more Smart Citation